Robotics and Cyborgs - Lumbreras Sancho, Sara (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
One of the main challenges of transhumanism is found in its anthropology. We are faced with a reductionism in which the body appears stripped of its dignity and the spirit does not exist. The example that most catches my attention of this is that of endogenesis: the fact that the human being is gestated inside the womb of another human being is not valued; for them it would be preferable to have a machine that could do the same mission, instead of the pregnancy being an act of love that has an impact on the whole life of the person. I think this is the biggest obstacle we will find ourselves in when valuing transhumanism, and it is especially important: the person is a building of multiple dimensions (physical, psychic, spiritual ...) inextricably linked. It is necessary to recognize the dignity of our body, which goes beyond being a material substrate of our consciousness. The body is part of our nature, in which body, emotion, thought and spirit are dimensions that are intimately linked. We cannot give up our body. In addition, I would like to propose that within the body there are portals to transcendence. being is not the same as appearing. Many argue that soon we will have robots that will be endowed with consciousness. That they will be able to pass the Turing test. In addition, Artificial Intelligence (AI) allows to generate messages synthetically. In some cases, these messages are relatively simple, but in other cases, such as chatbots (robots designed to chat), they are very interesting. Some authors estimate that these chatbots could soon pass the Turing test (that is, manage to convince a human interlocutor that he is conversing with another person). Once we have machines that pass the Turing test, can we say that they are conscious? Is a machine that passes the Turing test the same as a conscious machine? For some, the answer is «it doesn’t matter». I say no, it is not the same.